2016
DOI: 10.1016/j.molp.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

SUVH2 and SUVH9 Couple Two Essential Steps for Transcriptional Gene Silencing in Arabidopsis

Abstract: In Arabidopsis, an RNA-directed DNA methylation pathway (RdDM) is responsible for de novo establishment of DNA methylation and contributes to transcriptional gene silencing. Recently, the microrchidia (MORC)-type ATPases were shown to play essential roles in enforcing transcriptional gene silencing of a subset of genes and transposons by regulating the formation of higher-order chromatin architecture. However, how MORC proteins cooperate with the RdDM pathway components to regulate gene expression remains larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 61 publications
3
54
0
Order By: Relevance
“…Mutants with severe methylation defects, clustering with nrpe1-11 , include NRPE1 with the full CTD deleted (Δ1251–1976), NRPE1 missing the DeCL and QS subdomains (Δ1736–1976) and several mutants defective for proteins implicated in Pol V recruitment to target sites, including drd1 , dms3 , and suvh2 suvh9 (Jing et al, 2016; Johnson et al, 2014; Liu et al, 2014; Wierzbicki et al, 2008; Wierzbicki et al, 2009; Zhong et al, 2012) (Figure 4A, Table S2). Mutants with less severe effects on methylation, resembling CTD deletion mutants lacking the linker, 17 aa repeat, or QS subdomains, include mutants defective for proteins that interact with Pol V transcripts and/or Pol V transcription elongation complexes, including the IDN2-IDP complex ( idn2 idnl1 idnl2 ) , spt5L ( also known as ktf1) , and rrp6L1 , (Ausin et al, 2009; Bies-Etheve et al, 2009; He et al, 2009; Kollen et al, 2015; Rowley et al, 2011; Zhang et al, 2012) (Figure 4A, Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Mutants with severe methylation defects, clustering with nrpe1-11 , include NRPE1 with the full CTD deleted (Δ1251–1976), NRPE1 missing the DeCL and QS subdomains (Δ1736–1976) and several mutants defective for proteins implicated in Pol V recruitment to target sites, including drd1 , dms3 , and suvh2 suvh9 (Jing et al, 2016; Johnson et al, 2014; Liu et al, 2014; Wierzbicki et al, 2008; Wierzbicki et al, 2009; Zhong et al, 2012) (Figure 4A, Table S2). Mutants with less severe effects on methylation, resembling CTD deletion mutants lacking the linker, 17 aa repeat, or QS subdomains, include mutants defective for proteins that interact with Pol V transcripts and/or Pol V transcription elongation complexes, including the IDN2-IDP complex ( idn2 idnl1 idnl2 ) , spt5L ( also known as ktf1) , and rrp6L1 , (Ausin et al, 2009; Bies-Etheve et al, 2009; He et al, 2009; Kollen et al, 2015; Rowley et al, 2011; Zhang et al, 2012) (Figure 4A, Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…However, in this case, the methylated DNA is recognized directly by the methylcytosine binding proteins, SUVH2 and SUVH9 (Johnson et al 2008; Johnson et al 2014; Liu et al 2014; Jing et al 2016; Liu et al 2016). These proteins are members of the histone methyltransferase family that have SRA domains for binding methylated DNA as well as domains for methylating histone H3 within associated nucleosomes.…”
Section: How Do Pols IV and V Know Where To Transcribe?mentioning
confidence: 99%
“…In contrast, pre‐SET/SET/post‐SET domains in SUVH2 and SUVH9 have no methyltransferase activity, but interact with the DDR complex and mediate Pol V recruitment in the RdDM pathway (Johnson et al ; Liu et al ). They also interact with MORC proteins to recruit a chromatin‐remodeling complex to condense chromatin (Jing et al ). Our work here showed that SUVH1, SUVH3, SUVH7 and SUVH8 have critical roles in anti‐silencing.…”
Section: Discussionmentioning
confidence: 99%